Strategic Competitiveness Enhancement of a Local Business Hotel: A Data-Driven SWOT and QSPM Approach at Permata Hotel Bogor - Rina Dwi Kristiani; Suci Sandi Wachyuni; Dewi Ayu Kusumaningrum (Green Publisher Indonesia, 2026)
This study aims to formulate competitive strategies for Permata Hotel Bogor as a local business hotel in response to increasing competition and the ongoing digital transformation in the hospitality industry. The research adopts a mixed-method approach with a sequential exploratory design, combining qualitative insights, customer perceptions derived from online reviews, and quantitative strategic analysis. Data were collected through in-depth interviews, Focus Group Discussions (FGD), observation, and documentation. In addition, customer reviews were analyzed using R Studio through text mining and sentiment analysis to identify key issues, sentiment intensity, and their impact on customer satisfaction. The identified factors were then evaluated using IFAS and EFAS matrices, followed by SWOT analysis, and prioritized using the Quantitative Strategic Planning Matrix (QSPM). The findings show that strengthening digital marketing and optimizing Online Travel Agent (OTA) channels is the top priority strategy (TAS = 3.07), followed by market diversification (2.87) and facility modernization (2.68). Overall, this study highlights the importance of adopting a data-driven strategic approach to enhance competitiveness in the hospitality industry.